Genetic Variation of Methylenetetrahydrofolate Reductase (MTHFR) and Thymidylate Synthase (TS) Genes Is Associated with Idiopathic Recurrent Implantation Failure - Choi, Youngsok; Kim, Jung Oh; Shim, Sung Han; Lee, Yubin; Kim, Ji Hyang; Jeon, Young Joo; Ko, Jung Jae; Lee, Woo Sik; Kim, Nam Keun (PloS one, 2016)
The one-carbon metabolism pathway disorder was important role in successful pregnancy. The MTHFR and TS protein were crucial factor in one-carbon metabolism. To investigate the association between recurrent implantation failure (RIF) and enzymes in the one-carbon metabolism pathway. A total of 120 women diagnosed with RIF and 125 control subjects were genotyped for MTHFR 677C>T, 1298A>C, TSER 2R/3R and TS 1494del/ins by a polymerase chain reaction-restriction fragment length polymorphism assay. According to the gene-gene combination analysis, the MTHFR 677/MTHFR 1298 (TT/AA) and MTHFR 677/TS 1494 (TT/6bp6bp) genetic combinations were associated with relatively higher risks [adjusted odds ratio (AOR), 2.764; 95% CI, 1.065-7.174; P = 0.037 and AOR, 3.186; 95% CI, 1.241-8.178; P = 0.016] in RIF patients compared to the CC/AA (MTHFR 677/MTHFR 1298) and TT/6bp6bp (MTHFR 677/TS 1494) combinations, respectively. The results suggested that the combined MTHFR 677/MTHFR 1298 genotype might be associated with increased risk of RIF. To the best of our knowledge, this study is the first to elucidate the potential association of MTHFR, TS and TSER polymorphisms with RIF risk in Korean patients.